Metabolomic signature and mitochondrial dynamics outline the difference between vulnerability and resilience to chronic stress - Paola Brivio; Matteo Audano; Maria Teresa Gallo; Piotr Gruca; Magdalena Łasoń; Ewa Litwa; Fabio Fumagalli; Mariusz Papp; Nico Mitro; Francesca Calabrese (2022)
Abstract Stress is the foremost environmental factor involved in the pathophysiology of major depressive disorder (MDD). However, individual differences among people are critical as some people exhibit vulnerability while other are resilient to repeated exposure to stress. Among the others, a recent theory postulates that alterations of energy metabolism might contribute to the development of psychopathologies. Here we show that the bioenergetic status in the ventral hippocampus (vHip), a brain subregion tightly involved in the regulation of MDD, defined the development of vulnerability or resilience following two weeks of chronic mild stress. Among the different metabolomic signatures observed, the glycolysis and tricarboxylic acid cycle may be specifically involved in defining vulnerability, revealing a previously unappreciated mechanism of sensitivity to stress. These findings point to mitochondrial morphology and recycling as critical in the ability to cope with stress. We show that vulnerable rats favor mitochondrial fusion to counteract the overproduction of reactive oxidative species whereas resilient rats activate fission to guarantee metabolic efficiency. Our results indicate that the modulation of the energetic metabolite profile in vHip under chronic stress exposure may represent a mechanism to explain the difference between vulnerable and resilient rats, unraveling novel and promising targets for specific therapeutic interventions.